Internationalization, Whiteness, and Biopolitics of Higher Education - Suspitsyna, Tatiana (Journal of International Students, 2021)
From a postcolonial perspective, U.S. higher education is entangled with the colonial past and the neoliberal neo-colonial present as an economic actor that dominates global educational markets through internationalization. The COVID pandemic and the nationwide movement for racial justice have brought these entanglements into stark relief in the ways U.S. colleges and universities are implicated in the neoliberal biopolitics of race. Applied to higher education, Michel Foucault’s concept of biopolitics as the management of life and wellbeing of populations and his conceptualization of racism as a biopolitical tool illuminate how U.S. colleges and universities maintain racialized categorizations of lives worth protecting and lives considered disposable in the service of dominant whiteness. De-centering whiteness and eliminating its advantage and superiority in research, curricula, instruction, and internationalization is a necessary step toward a future that envisions a more inclusive and equal citizenship.